Enzymes in Peri-implant Sulcular Fluid: A Window into Periodontal Health - A Comprehensive Review - Kumar Gautham; Natarajan Prabhu M; Al Shayeb Maher A. F (Wolters Kluwer Medknow Publications, 2024)
Enzymes in peri-implant sulcular fluid (PISF) have emerged as essential biomarkers in the field of periodontics, providing critical insights into the health and stability of dental implants. This essay explores the significance of various enzymes in PISF, including matrix metalloproteinases (MMPs), elastase, alkaline phosphatase, acid phosphatase, aspartate aminotransferase (AST), and alanine aminotransferase (ALT), in assessing the local inflammatory environment and diagnosing peri-implant diseases. The analysis of these enzymes facilitates early detection of complications, personalized treatment planning, and long-term monitoring, emphasizing the need for a multidisciplinary approach to patient care. Collaboration among dental professionals and patient education is crucial in ensuring the successful management and maintenance of dental implants. Understanding the role of enzymes in PISF and their implications in periodontal health underscores their significance in contemporary periodontics and emphasizes the need for ongoing research and technological advancements.